Transformasi Dakwah Islam Moderat di Era Digital: Peran Muballigh NU dan Muhammadiyah dalam Menangkal Radikalisme Agama: Peran Muballigh NU dan Muhammadiyah dalam Menangkal Radikalisme Agama - Thiyas Tono Taufiq; Muhammad Faiq; Moh. Hadi Subowo (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2025)
The religious radicalism in Indonesia is growing immensely with the huge application of digital technology, particularly social media, as a novel platform for spreading extremist religious ideology. Moderate preaching has become an important approach in countering the spread of radicalism in this context. This article examines how moderate da'wah is reconstructed by preachers (muballigh) of two major Islamic organizations, namely Nahdlatul Ulama (NU) and Muhammadiyah, in addressing da'wah challenges in the digital era. This study employs a qualitative methodology with a virtual ethnographic style to observe the da'wah content disseminated by NU and Muhammadiyah preachers through social media. The results of the study indicate that NU and Muhammadiyah preachers have changed their da'wah methods by utilizing digital media such as Instagram and TikTok as a platform for disseminating Islamic messages that are tolerant, inclusive, and anti-violent. The methods implemented include building contextual religious discourses, adopting cultural approaches, and engaging in active participation in interfaith dialogue and societal engagement. This shift indicates that moderate da'wah is not only capable of keeping pace with technological advancements but also plays a significant role in advancing peaceful religious consciousness within the digital public sphere. This article recommends the importance of institutional support and enhancing the digital capabilities of religious educators to make moderate da'wah more effective in countering religious radicalism.